Nutritive value of three tropical legume forage - Nascimento, Hoston Tomás Santos do; Nascimento, Maria do P. S. C. Bona do (Pesquisa Agropecuaria Brasileira, 1991)
The protein, phosphorus, and calcium contents, and the in vitro dry matter digestibility IVDMD percent of Cratylia floribunda, Canavalia obtusifolia and Dioclea lasiophylla were determined. The plants were grown in pots, in a greenhouse. The experimental design was a completely randomized block, with three replications, in a 5 x 3 factorial, being five cutting dates (15, 21, 30, 45 and 60 days old plants) and three species of plants. The protein percent ranged from 17.5 to 30.4%; 9.6 to 16.5% and from 20.2 to 29.9% for D. lasiophylla, C. obtusifolia and C. floribunda, respectively. The phosphorus contents ranged from 0.22 to 0.33%; 0.09 to 0.25% and from 0.17 to 0.28%, whereas the calcium contents ranged from 1.32 to 2.10%; 1.30 to 2.50% and from 1.54 to 2.10%. The highest IVDMD was found in C. obtusifolia (67.3 to 78.1%), followed by C. floribunda (60.6 to 69.0%) and by D. lasiophylla (51.2 to 61.4%).
Keywords: Cratylia floribunda; Canavalia obtusifolia; Dioclea lasiophylla; protein; phosphorus; calcium; digestibility